ANALYZE THE ACCURACY AND PRECISION OF SLIP-ON SPROCKETS - HARBHAJAN SINGH, ALWINJEET SINGH (IRC, 2021)
The sprocket system is a mechanical device that is commonly used to transmit power and torque in most vehicles.